Analysis of English Textbook for Third-Grade in Senior High School - Ratu Amalia Awal; Amirullah Abduh; Abdul Halim (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This research aims to find out whether the textbook is eligible for students based on the National Education Standards Agency (BSNP), to find out the benefits of textbooks used by teachers in third grade, and to find out the difficulties faced by teachers in using textbooks. This research used the descriptive analysis method with a qualitative approach. This research used two instruments. First, this study used four indicators of book eligibility based on the National Education Standards Agency (BSNP). Second, it used the interview technique of teachers to find out the benefits of textbooks used for third-grade students and to find out the difficulties of teachers in using textbooks used in learning. The results of the research indicate that the textbook entitled “Bahasa Inggris Kelas XII SMA (Kementrian Pendidikan dan Kebudayaan Republik Indonesia) Edisi Revisi 2018” included in the decent category in terms of The Eligibility of Content, The Eligibility of presentation, The Eligibility of Language and The Eligibility of Graphics. For teachers and students, this textbook is very useful because it can be a guide for teachers in delivering materials and is also a source of learning for students. Other than that, the materials presented in this textbook also fit students' needs, and the language used is quite well and easy to understand. Moreover, the material presented in this textbook is already following the standard competency and basic competency. Meanwhile, the difficulty facing teachers in using this textbook is that it is not equipped with listening material and it is also limited to school libraries.